Inspirational soundtrack as demonstrates in Christian film in USA - Ngui, Yew Fong (Universiti Malaysia Sarawak (UNIMAS), 2015)
The research is about the isnpiration of the soundtrack in a film to give motivation to the audience. In this research, the researcher will understand more about the history of the sound and the development of the music soundtrack in the film. Besides, the researcher would like to see how the music soundtrack communicates emotion and how the instpirational music in the film motivates people. The music can motivate people, and the emotion of people will differ when hearing the music. The researcher would like to rediscover the importance of the music in the film and how does the selection of music affect the emotions of the spectator.